2016
DOI: 10.1177/0891243216681494
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Chilly Climate

Abstract: The prevailing metaphor for understanding the persistence of gender inequalities in universities is the "chilly climate." Women faculty sometimes resist descriptions of their workplaces as "chilly" and deny that gender matters even in the face of considerable evidence to the contrary. I draw on interviews with women academics (N=102) to explore this apparent paradox, and I offer a theoretical synthesis that may help explain it. I build on insights from Ridgeway and Acker to demonstrate that women do experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(59 citation statements)
references
References 37 publications
4
52
0
3
Order By: Relevance
“…In this way, instead of presenting 'resistant' selves, academics are inclined to comply with or conform to the demands of the performance culture (Clarke & Knights, 2015, p. 1879. This finding helps to further explain why previous research has found that gender inequities are felt more keenly at some moments rather than others and is viewed as subtle rather than oppressive (see Britton, 2017). In this organizational context, women internalize the game and do not always question the mechanisms that erode their entitlements and make claim on their family time.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In this way, instead of presenting 'resistant' selves, academics are inclined to comply with or conform to the demands of the performance culture (Clarke & Knights, 2015, p. 1879. This finding helps to further explain why previous research has found that gender inequities are felt more keenly at some moments rather than others and is viewed as subtle rather than oppressive (see Britton, 2017). In this organizational context, women internalize the game and do not always question the mechanisms that erode their entitlements and make claim on their family time.…”
Section: Discussionmentioning
confidence: 55%
“…Our analysis has attempted to think through the 'subtle and persistent' ways in which women academics are disadvantaged (Britton, 2017). Future research needs to generate further understandings of how discursive new managerial power operates in our universities in order to help us to work towards more successfully implemented equal opportunity policies (Bagilhole, 2002, p. 21).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have found that women often ignore, or altogether dismiss, sexism at work in some work contexts (Bird & Rhoton, 2011;Britton, 2017;Harris & Giuffre, 2015;Irvine & Vermilya, 2010;Rhoton, 2011). Britton's (2017) study of women faculty identified a paradox: Despite their recognition of gender inequalities and biases, women said that gender does not matter at work and downplay its ubiquity. Several respondents described interactions when they were "blindsided" by the "salience" of gender.…”
Section: Lack Of Recognition Of Gender Inequality At Workmentioning
confidence: 99%
“…The intersection between gender and age has been particularly neglected, not only among professions scholars, but in intersectionality theory as well (McMullin, 2011;Choroszewicz & Adams, 2019). Professions, and the organizations in which professionals work, are gendered institutions (Adams, 2000;Britton, 2017;Davies, 1996). Historically, male-dominated professions were designed by men for men, and women have been at a disadvantage-experiencing discrimination, and barriers respecting entry, promotion, and practice opportunities (Davies, 1996;Hearn, Biese, Choroszewicz & Husu, 2016;.…”
Section: Resultsmentioning
confidence: 99%
“…Research has explored the movement of women into traditionally male-dominated professions (Adams, 2010;Choroszewicz & Kay, in press), as well as women and men's different experiences of career entry, career progression, professional practice and identity, and work-family reconciliation (see for example Choroszewicz & Adams, 2019). Despite the feminization trend in Western professions, gender equity social policies, and other social change, there is evidence that gender still shapes experiences of professional employment in important ways (Britton, 2017;Hearn et al, 2016). However, it has also become clear that a gender lens is often insufficient as social inequalities across a range of dimensions, including class, race/ethnicity, sexual orientation, and citizenship, intertwine to shape experiences (Choroszewicz & Adams, 2019;Holvino, 2010).…”
Section: Intersectionality and Life Course Perspectivementioning
confidence: 99%